Analisis Peran Kemajuan Teknologi, Kelembagaan dan Nilai Tukar Rupiah dalam Menopang Neraca Perdagangan Indonesia: Pendekatan Autoregressive Distributed Lag (Ardl) - Amelia Anjani; Prof. Dr. Nairobi, S.E., M.Si.; Rizka Malia, S.E., M.E. (CV. ITTC INDONESIA, 2026)
The trade balance is an important indicator of Indonesia’s external sector performance. This study examines the effects of Research and Development (R&D) Expenditure, regulatory quality, and the rupiah exchange rate on Indonesia’s trade balance during 1995–2024. A quantitative approach was employed using annual time-series data obtained from the World Bank, Worldwide Governance Indicators, and Bank Indonesia. The Autoregressive Distributed Lag (ARDL) model was applied to estimate short-run dynamics and long-run relationships, while the Impulse Response Function (IRF) was used to evaluate the response of the trade balance to shocks in each explanatory variable. The results show that, in the short run, regulatory quality and the rupiah exchange rate have negative and significant effects on the trade balance, whereas R&D Expenditure has a positive and significant effect. In the long run, R&D Expenditure has a positive and significant effect, while regulatory quality and the rupiah exchange rate have negative and significant effects. The IRF results indicate that shocks to the rupiah exchange rate generate the largest response in Indonesia’s trade balance. These findings highlight the importance of strengthening long-term innovation capacity while maintaining effective regulation and exchange-rate stability.